SOLUTION:
Step 1:
In this question, we are given the following:
Write an equation of a line that is parallel to the line whose equation is
![\text{3 y = x + 6}](https://img.qammunity.org/2023/formulas/mathematics/college/7w7kjy4th2aqejahetv5ggwcvc9di9w3lu.png)
and that passes through the point (-3,4)
Step 2:
From the question, we can see that the given equation is given as:
![\begin{gathered} 3\text{ y = x + 6} \\ \text{Divide both sides by 3, we have that:} \\ y\text{ = }(1)/(3)x\text{ + 2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zo8n4cpulnjc5uln0ckych9q00nxgvocjf.png)
Comparing this, with the equation of a line, we have that:
![\begin{gathered} y\text{ = mx + c} \\ \text{Then, the gradient of line, m = }(1)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yq1kywfk5qokaw5aeobphauh1kyesmzfyb.png)
Step 3:
Now, using the equation of a line:
![\begin{gathered} y-y_1=m(x-x_1) \\ \text{where (x }_1,y_1)\text{ = ( -3 , 4 )} \\ m\text{ = }(1)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/h32gxfws612mt7mgyyav1akou366cvwilo.png)
![\begin{gathered} y\text{ - }4\text{ = }(1)/(3)(\text{ x -- 3)} \\ y\text{ - 4 =}(1)/(3)(\text{ x+ 3)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zff0oyp074fni2ugpvvxf6h6sf0g57xhca.png)
Multiply through by 3, we have that:
![\begin{gathered} \text{3 ( y - 4 ) = ( x + 3)} \\ 3y\text{ - 12 = x + 3} \\ \text{Hence, we have that:} \\ 3y\text{ = x + 3 +1 2} \\ 3\text{ y = x + 15} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/f3c4e8ynnxx31q3gtnta8nl85di8fxsant.png)
CONCLUSION:
The equation of the line that is parallel to the given line is:
![3y\text{ = x + 15}](https://img.qammunity.org/2023/formulas/mathematics/college/vfcgdv2ob2wi2bhrxr0a0ayciallg73mck.png)